Yield and yield components of tomato (Solanum lycopersicum) selected through pedigree method in the lowlands, Bogor-Indonesia - Prakoso Mawasid, Fajar (2024)
Introduction. Segregated populations can exhibit fluctuating yields from one generation to the next. This can sometimes perplex plant breeders when interpreting observed phenomena and determining which selection methods to choose. Objective. To analyze the performance and yield components of several tomato (Solanum lycopersicum) populations selected through the pedigree method in lowland environments in Bogor, West Java, Indonesia. Materials and methods. This study was conducted from December 2018 to April 2019 at the Experimental Garden of Bogor Agricultural University, Tajur II (207 meters above sea level), Bogor, West Java, Indonesia. Four generations were utilized, derived from 99D×Tora, i.e., 200 plants from the F2 generation and 100 plants each from the F3, F5, and F6 generations, respectively. Results. Population variance in terms of yield and yield components, as well as heritability, were lower in later generations compared to earlier generations. An increase in mean value was observed in the F3 generation, but decreased in the F5 and F6 generations across all observed traits. This could be attributed to fixation resulting from the elimination of epistatic genes that played a role in environmental stress. Conclusion. Pedigree selection in early generation was not suitable in lowland. It is suggested to evaluate mass selection methods or single seed descent, as these methods were able to maintain population variance into later generations.